Phonetic Comparative Analysis: 'Amiya Levant vs Arab Fusha in The Album Bi Saraha by Abeer Nehme - Fauzan Hakami; Miatin Rachmawati; Jelita Nurhaliza Kusuma Jaedi; Nafisa Hakami (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2025)
This study explored the phonetic contrasts between Arabic Fusha and the Levantine dialect ('Amiya) in Abeer Nehme's album, Bi Saraha. By analyzing seven songs through a comparative approach, it identifies 180 phonetic transformations, including lenition, fortition, sound loss, sound addition, metathesis, assimilation, and tone changes. These variations highlight differences in consonant substitution, vowel simplification, and intonation, showcasing the flexibility and emotional resonance of 'Amiya in contrast to the formality of Fusha. The findings emphasize the geographic, cultural, and linguistic influences that reveal 'Amiya's adaptability for daily communication and musical expression. Utilizing the theories of Crowley and Chaer, the study explains these changes as responses to articulation efficiency, regional norms, and aesthetic needs. This research contributes to the field of Arabic linguistics by providing insights into dialectal phonetics and their interaction with cultural contexts, thereby encouraging further exploration of morphological and semantic aspects.